PENGARUH BELANJA TIDAK TERDUGA TERHADAP DEFISIT KEUANGAN DAERAH PERIODE ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) 2019-2020 DI KABUPATEN TRENGGALEK - Erlin Anggrista Aprilia; Muhammad Farid Ma’ruf (Publika, 2022)
The use of APBD in each region has different proportions depending on the priorities of each region. However, unexpected events have resulted in the regions having to adjust their current APBD so that they do not affect other sectors. This study aims to test and find out whether there is an influence between spending not on the 2019-2020 regional budget deficit in Trenggalek Regency. This study uses quantitative research methods with a correlation approach so that the correlation between variables will be seen. The sampling technique was carried out with the Saturated Sampling technique, the researchers used this technique because the population in the study was not too large, namely the 2019-2020 budget period. The data collection technique used a documentation technique whose data was taken from the official website of the Trenggalek Regency Government. The data processing technique uses a simple linear regression technique so that it can be seen that there is a correlation between unexpected spending and the regional financial deficit of the Trenggalek Regency Government Budget. The 2019-2020 Trenggalek Regency APBD period is considered very complex, the APBD always experiences a surplus but at the end of the period there is a reshuffle of the APBD caused by the COVID-19 pandemic. Then with this problem the question arises, is there an influence or not between the two variables. With this research, it is hoped that it can become additional literature for the regions so that they can make good use of their regional budgets. After knowing the correlation of unexpected spending with regional financial deficits, the regions will be more careful to use the APBD. This is due to the fact that the APBD is not only used as a regional financial table but also as a benchmark for the success of the region in regulating and utilizing the potential of the region it has.